Collective action for sustainable water harvesting irrigation - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Collective action for water harvesting irrigation (WHI) refers to the joint or collective effort of farmers in getting and using water for crop, animal, household, or other purposes. Organized water user groups also handle external representation with government programs and external demands (either competing or complementary) for water and other resources. In water-scarce areas, the goal is for farmers to produce high crop yields with less water, which can be achieved when farmers collectively manage the water resources available to them.